Embedding Sustainability Throughout a Traditional MBA Program - Harmon, Joel (Archīum Ateneo, 2024)
With the many urgent problems facing our society, it has become imperative that we change the way we educate current and future business leaders. Here we share an approach we have taken for the MBA program at Fairleigh Dickinson University in the hope that it may be instructive for others seeking to make sustainability a central theme in their curriculum. Our goal is to develop the motivation, mindset, and toolset of faculty and students to make a positive difference in the world. While sustainability is probably best treated as a theme woven throughout a curriculum (rather than as a single standalone course), it may be necessary to create a broad sustainability foundation course for students so that it will be feasible for faculty to pick up on, extend, and deepen relevant topics appropriate for their individual discipline-focused courses. We describe the content of such a course and the process we used for engaging faculty. We believe our approach represents a pragmatic first step toward making sustainability more central and weaving it into a curriculum. By bringing faculty along who may not have been previously exposed to sustainability topics and getting them to start introducing these into their courses, and by exposing students to core sustainability ideas and mindsets right at the beginning of their MBA program while encouraging them to demand pro-actively for deeper consideration of such in later courses, we may create the conditions for more ambitious transformation in the future.